Local Government Dependence, Capital Expenditure, and Transparency Level: Moderating Role of Local Government Size - Amrie Firmansyah; Danang Andrian Mubarok; Ni Wayan Sintya Galuh Paramita (Politeknik Keuangan Negara STAN, 2023)
Research objective: this research aims to examine the influence of local governments dependence and capital expenditure on the local government's transparency level including the influence of local government's size as moderating variable in the association. Method: According to the purposive sampling technique, the sample selected in the study is nine local governments in Bali. The data were collected by accessing the local government's official website to search for financial information from 2016 to 2020. Hypothesis testing was conducted by multiple regression analysis for panel data. Research finding: the results show that local government dependence and capital expenditure negatively affect local government transparency while local government size has no moderating effect on the relationship between variables. Practical implication: this study suggests that the Indonesian Ministry of Home Affairs should enhance the supervision for improving the local governments’ financial information transparency.